Synthesis and evaluation of novel heterocycles as potential HIV-1 enzyme inhibitors - Ngnie Tuemgnie, Gaëlle Tatiana (Rhodes University, Faculty of Science, Department of Chemistry, 2014)
This project has focussed on the synthesis and the evaluation of organic compounds as potential HIV-1 enzyme inhibitors, by making use of green chemistry (microwave assisted synthesis and click chemistry), palladium catalyzed reactions (Heck and Sonogashira coupling), Baylis Hillman methodology and aldol condensation. These compounds were synthesized in good yields and fully characterised by spectroscopic techniques. Biological assay data revealed that some of the compounds possess high inhibitory activity and their effective inhibitory concentration was as good as those of drugs in clinical use. These potential drug molecules were identified by preliminary investigations carried out by molecular modelling where a trend of their inhibitory activity against different enzymes was anticipated. Benzotriazole-AZT conjugates generated by 1,3-dipolar cycloaddition of anthranilic acid derivatives with AZT showed good inhibitory activity in silico against both HIV-1 protease (PR) and HIV-1 reverse transcriptase (RT) enzymes. Still in line with our dual action strategy, cinnamate ester-AZT conjugates were synthesized in three steps starting from benzaldehyde derivatives with a click reaction at the final step. These compounds also showed some inhibitory activity against HIV-1 RT enzyme (88%). In addition, the cinnamoyl fragment attached to AZT appeared to improve the activity of AZT against HIV-1 RT. Peptide chemistry involving carbonyl diimidazole as a coupling reagent between cinnamic acid derivatives and protected amino acids was used to prepare substituted amino acid derivatives which appeared to be very active against the integrase (IN) enzyme (88%). Commercially available coumarin was iodinated and derivatized through palladium catalyzed Heck and Sonogashira reactions with activated alkenes and a terminal alkyne respectively to afford novel coumarin derivatives in good yields. Optimization studies on the Heck reaction with regards to the phosphine ligand, the palladium catalyst and the solvent were carried out to afford novel formyl substituted cinnamate esters with nonaflyl salicylaldehyde derivatives.
Keywords: Heterocyclic compounds; Enzyme inhibitors; Organic compounds; Green chemistry; Coumarins; HIV (Viruses) Enzymes